ANALISIS YURIDIS TERHADAP KONVERSI BANK KONVENSIONAL MENJADI BANK BANK SYARIAH PADA PT BANK ACEH SYARIAH - ADE YATSYAH BASUKI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. H.M. Hasballah Thaib, MA, PhD2. Dr. Utary Maharany Barus, SH, MHum3. Dr. Idha Aprilyana Sembiring, SH, MHumConventional bank conversion into sharia bank is regulated in accordance with the prevailing laws and regulations in Indonesia which says that conversioncan be done by some ways, namely thorough bank conversion, bank acquisition ortakeover, Sharia business unit conversion, and by spin off or bank division.The conversion procedure in PT Bank Aceh Syariah is done thoroughly.The legal consequences caused by the conversion is the change in the legalregulations of PT Bank Aceh Syariah which is previously operated based on theLaw No. 10/1998 in conjunction with the Law No. 7/1992 concerning Banking, itis now operated based on the Law No. 21/2008 concerning Sharia Bank.The institutional change of the Bank is indicated by changes in thecompany name and organization Structure of PT Bank Aceh Syariah. The changein products is indicated by the change in products from conventional system intosharia system.Keyword: Conversion, Bank, Conventional, Sharia.